United States : Publication of Financial Sector Assessment Program Documentation; Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2010)
Though The United States has experienced a devastating financial crisis owing to multifaceted factors, it started showing recovery. The authorities welcomed the program, which included strengthening microprudential regulation, establishing macroprudential responsibilities, strengthening market discipline, and reforming credit policies. They emphasized the need to establish a council of regulatory agencies such as the Federal Reserve and the Treasury, with a mandate for financial stability. They stressed the need to enhance crisis management, resolution, and systemic liquidity arrangements, and also to address too-big-to-fail issues and the future of the government-sponsored enterprises (GSEs).